ENGINEERING PEDAGOGY: FACING TYPOLOGY CHALLENGES - V. G. Ivanov; Z. S. Sazonova; M. B. Sapunov (Высшее образование в России)
In the paper, the authors ponder on conceptual prerequisites and foundations of engineering pedagogy, thereby, the study has a problem-oriented and reflective character. The purpose of the paper is to set a problem ofthe status of engineering pedagogy, to propose a metatheoretical level of its consideration, and to invite the researchers for further discussion. Training of technical university teachers in engineering pedagogy is a prerequisite of advanced higher technical education. Because of this, reflections on engineering pedagogy have involved many Russian researchers. The analysis of papers published in the journal Higher Education in Russia for the last ten years has enabled the authors to regard engineering pedagogy in the following three aspects (dimensions): 1) as a pedagogical technique emerging in a technical university teacher's activities; 2) as a discipline taught at different levels ofhigher education and in professional development courses aimed at training technical university teachers; and 3) as a field of study (and the corresponding specialty). This approach allows to define the aims and objectives of engineering pedagogy in a systematic and multidimensional way. Since technical university teachers are expected to obtain pedagogical, methodological and research competences, developing and practicing engineering pedagogy enable them to perform as teachers, methodologists and researchers in their unity and diversity.